2022
DOI: 10.48048/tis.2022.5763
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Zinc Vanadate Nanostructures for Supercapacitor Applications

Abstract: A simple hydrothermal approach was used to successfully produce nanostructured Zinc vanadate (Zn3V2O8), which was calcined at 450 ℃. The structural, optical and surface morphological features of calcined Zn3V2O8 nanoparticles were investigated using a variety of analytical techniques. The produced Zn3V2O8 nanoparticles had an orthorhombic crystalline structure, with an average crystallite size of 35.14 nm, according to the X-ray diffraction pattern (XRD). Transmission electron microscopy (TEM) analysis evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…4 b showed that the strong and maximum intense XRD peaks at 35.73° and 44.07° attributed to (221) and (240) planes, respectively, attributed to the Ni 3 V 2 O 8 (JCPDS card No. 70–1394) [ 3 , 23 , 57 ]. It is well known that at a higher calcination temperature, the nickel-vanadium phase would transfer to other phases [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 b showed that the strong and maximum intense XRD peaks at 35.73° and 44.07° attributed to (221) and (240) planes, respectively, attributed to the Ni 3 V 2 O 8 (JCPDS card No. 70–1394) [ 3 , 23 , 57 ]. It is well known that at a higher calcination temperature, the nickel-vanadium phase would transfer to other phases [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their higher ionic conductivity and rapid proton mobility contribute to their lower internal resistance, rendering them desirable candidates [15]. Already the electrochemical behavior of a vanadium based-based mixed metal oxide compounds were investigated using the hydrothermal method, revealing its high reversibility and an energy storage capacity [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudocapacitive materials, mostly transition metal oxides and electrically conductive polymers, could reach the same energy density as batteries and the same cycle life and power density as EDLCs. RuO 2 , NiO, MnO 2 , and V 2 O 5 are all examples of transition metal oxides with high theoretical pseudocapacitance [12][13][14][15] due to their many oxidation states for oxidation and reduction. For their high theoretical specific capacity and outstanding electrochemical reversibility, vanadium-based materials were among the most promising electrode materials for use in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel, being the most recently discovered transition metal in the Earth's crust, forms the backbone of modern infrastructure. One family of mixed metal oxides (AxByOz) is the binary metal oxides, also known as transition metal vanadates (MxVyOz; M = Cu, Co, Ni, Zn, Fe) [16,17]. This sort of material has gained a lot of attention as an active electrode material in the field of pseudo-supercapacitors [18] because to its many oxidation states, layered structure, and synergistic interaction between the transition metal and vanadium.…”
Section: Introductionmentioning
confidence: 99%